Exosomes Regulate the Transformation of Cancer Cells in Cancer Stem Cell Homeostasis - Jiasheng Xu; Kaili Liao; Weimin Zhou (Stem Cells International)
In different biological model systems, exosomes are considered mediators of cell-cell communication between different cell populations. Exosomes, as extracellular vesicles, participate in physiological and pathological processes by transmitting signaling molecules such as proteins, nucleic acids, and lipids. The tumor’s microenvironment consists of many types of cells, including cancer stem cells and mesenchymal cells. It is well known that these cells communicate with each other and thereby regulate the progression of the tumor. Recent studies have provided evidence that exosomes mediate the interactions between different types of cells in the tumor microenvironment, providing further insight into how these cells interact through exosome signaling. Cancer stem cells are a small kind of heterogeneous cells that existed in tumor tissues or cancer cell lines. These cells possess a stemness phenotype with a self-renewal ability and multipotential differentiation which was considered the reason for the failure of conventional cancer therapies and tumor recurrence. However, a highly dynamic equilibrium was found between cancer stem cells and cancer cells, and this indicates that cancer stem cells are no more special target and blocking the transformation of cancer stem cells and cancer cells seem to be a more significant therapy strategy. Whether exosomes, as an information transforming carrier between cells, regulated cancer cell transformation in cancer stem cell dynamic equilibrium and targeting exosome signaling attenuated the formation of cancer stem cells and finally cure cancers is worthy of further study.